(untitled) (Bangladesh Journal of Medical Science, 2016)
Researchers have concluded that teams are capable of outstanding performances and are the primary unit of performance for organizations. However High Performance Teams (HPTs) are a rarity. The paper discusses and analyzes the literature reviews on Definitions, Trust & Confidence, Conflict and Selection Processes linked to HPTs. It is imperative to note that HPTs are needed and are necessary in any healthcare setting as it improves the quality of services. The authors link the necessity of HPTs in healthcare facilities. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.10-14